Demersal fish and shrimp abundance in relation to mangrove hydrogeomorphological metrics - Jamizan A.R.,; Chong, V.C. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Previous studies have found positive correlations between mangrove forest extent and fisheries yield but none of these univariate relationships provide a reliable estimate of yield from mangrove area. This study tests the hypothesis that the nursery ground value or natural production of fish and shrimps is related to the hydrogeomorphology settings of mangrove forests by using multivariate redundancy analysis (RDA). The hydrogeomorphological metrics of five mangrove forests imaged by satellite were measured using Geographical Information System (GIS). The RDA indicated that the metrics, including mangrove area, multiple waterways and creeks, mangrove-river interface, waterway surface area and sediment organic matter, influenced the diversity and abundance of fish and shrimps. Larger values of these metrics increase the abundance of economically important fish species of the families Lutjanidae, Haemulidae, Serranidae and economically-important penaeid shrimps. Sediment organic matter also significantly correlates with the distribution and abundance of fish that feed off the bottom such as the Leiognathidae, Clupeidae and Mullidae. Mangrove forests with combinations of large mangrove area, river surface area, high stream ordering and longest mangrove-river interface will provide greater role as nursery grounds for fish and shrimps.